2016
DOI: 10.1007/s00170-016-9046-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and optimization of weld bead geometry for electron beam welding of AISI 304 stainless steel

Abstract: Electron beam welding, though considered a sophisticated welding process, still requires the operator to first carry out several trial welds to find the right combination of welding parameters based on intuition and experience. This archaic method is often unreliable, leading to unproductive manufacturing lead time, man hours, quality control tests, and material wastage. The current study eliminates this "trial and error" method by providing a reliable model which can predict the right combination of weld para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Improving the manufacturing quality and assembly quality heavily raises the production cost, and the traditional “trial and error” method needs plenty of man hours. As such, an acceptable solution is the introduction of intelligent welding technology to improve the reliability of product and production efficiency [ 3 , 4 ]. For a given task, the intelligent welding system should eliminate the trial time substantially to specify welding parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the manufacturing quality and assembly quality heavily raises the production cost, and the traditional “trial and error” method needs plenty of man hours. As such, an acceptable solution is the introduction of intelligent welding technology to improve the reliability of product and production efficiency [ 3 , 4 ]. For a given task, the intelligent welding system should eliminate the trial time substantially to specify welding parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Because to the complex interrelationship between these welding parameters, it is hard to deduce an appropriate physics model in continuous welding process with changing parameters [ 5 ]. In recent decades, researchers have applied various mathematical models to build the relationship between multi-input and multi-output parameters, e.g., factorial design, linear and nonlinear regression, response surface methodology, and artificial neural network (ANN) [ 4 , 6 , 7 , 8 , 9 , 10 , 11 ]. These design of experiments (DOE) techniques apply to different areas according to the complex relationship between input and output parameters, and they achieve high accuracy and efficiency in modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Weld bead geometry features (WBGFs) can reflect the welding process parameters and are effective evidence to suggest how to optimize the latter. This is because the relationship between WBGFs and weld process parameters can be built with various models [ 9 , 10 , 11 ]. Thus, the real-time modeling of WBGFs is the really demanded technology for the effective control of weld formation especially and accurate metal deposition [ 12 , 13 ] during the multipass welding process.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, studies can be found that use design of experiments (DOE) and other statistical and numerical approaches to predict and optimize weld quality for different welding methods [14,[21][22][23][24][25][26][27][28]. Nevertheless, few studies can be found that optimize the interaction of product geometry and welding process.…”
Section: Introductionmentioning
confidence: 99%